Durability evaluation of adhesive tapes for building applications. (10th February 2018) - Fufa, Selamawit Mamo; Labonnote, Nathalie; Frank, Susanne; Rüther, Petra; Jelle, Bjørn Petter
Highlights: Durability tests and evaluation methods used for tapes used in building is discussed. Accelerated ageing procedures for tapes used for indoor and outdoor is proposed. Adhesive degradation and a consequent sliding of the tape across the wind barrier due to wind load. Possibility of using standard substrate to evaluate the actual substrate/interface property. Abstract: In the building sector, various adhesive materials are experiencing an increased usage for sealing of overlaps and joints between most commonly used building materials, around penetrations, pipes and windows for increasing the moisture tightness and the airtightness of buildings. Among the adhesive materials are adhesive tapes that are used to ensure adequate airtightness of a building and thus must be able to withstand severe environmental conditions without significant long-term deterioration. Durability test methods are needed to evaluate whether the tapes fulfill their performance requirements for the service life of the whole building. However, there is a lack of reliable test methods and evaluation procedures for tapes used for building applications. This study was performed to evaluate tape durability testing and evaluation methods, which hence form a basis for further improvements of the existing methods.